Statistical Description in the Turbulent Near Wake of a Rotating Circular Cylinder - Dol, Sharul sham; Azimov, Ulugbek; Martinuzzi, R. (World Academy of Science, Engineering and Technology, 2012)
Turbulence studies were made in the wake of a rotating circular cylinder in a uniform free stream. The interest was to examine the turbulence properties at the suppression of periodicity in vortex formation process. An experimental study of the turbulent near wake of a rotating circular cylinder was made at a Reynolds number of 9000 for velocity ratios, λ between 0 and 2.7. Hot-wire anemometry and particle image velocimetry results indicate that the rotation of the cylinder causes significant changes in the vortical activities. The turbulence quantities are getting smaller as λ increases due to suppression of coherent vortex structures.